1999
DOI: 10.1073/pnas.96.25.14276
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human telomerase in immortal human cells leads to progressive telomere shortening and cell death

Abstract: The correlation between telomerase activity and human tumors has led to the hypothesis that tumor growth requires reactivation of telomerase and that telomerase inhibitors represent a class of chemotherapeutic agents. Herein, we examine the effects of inhibition of telomerase inside human cells. Peptide nucleic acid and 2-O-MeRNA oligomers inhibit telomerase, leading to progressive telomere shortening and causing immortal human breast epithelial cells to undergo apoptosis with increasing frequency until no cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
343
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 508 publications
(359 citation statements)
references
References 50 publications
12
343
1
2
Order By: Relevance
“…The major limitation of telomerase inhibition is the time necessary for the telomeres to become critically short before the antiproliferative effects are observed. Several reports have shown, in fact, that inhibition of telomerase by either a dominant-negative protein or antisense oligonucleotides against hTR results effectively in death of tumor cells with short but not long telomeres (Hahn et al, 1999;Herbert et al, 1999;Zhang et al, 1999). A complementary strategy to block tumor cell growth is to use telomerase inhibition as a means to sensitize cancer cells to chemotherapeutic drugs or angiogenesis inhibitors (Kondo et al, 1998;Ludwig et al, 2001;Misawa et al, 2002;Chen et al, 2003;Tentori et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The major limitation of telomerase inhibition is the time necessary for the telomeres to become critically short before the antiproliferative effects are observed. Several reports have shown, in fact, that inhibition of telomerase by either a dominant-negative protein or antisense oligonucleotides against hTR results effectively in death of tumor cells with short but not long telomeres (Hahn et al, 1999;Herbert et al, 1999;Zhang et al, 1999). A complementary strategy to block tumor cell growth is to use telomerase inhibition as a means to sensitize cancer cells to chemotherapeutic drugs or angiogenesis inhibitors (Kondo et al, 1998;Ludwig et al, 2001;Misawa et al, 2002;Chen et al, 2003;Tentori et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of telomerase may lead to proliferation arrest in two ways: by eroding telomeres, which will eventually become too short to allow proper cellular division, and by a more direct effect on the telomere distal end, in which the enzyme no longer protects, thereby leading to immediate proliferation arrest. Shortening of telomeres as a result of different telomerase inhibitors leading to cellular senescence and apoptosis has been demonstrated in several reports (Hahn et al, 1999;Herbert et al, 1999Herbert et al, , 2002Izbicka et al, 1999;Damm et al, 2001;Boklan et al, 2002;Grand et al, 2002;Seimiya et al, 2002;Pang et al, 2003). The other protective function of telomerase, proposed by Blackburn and her group, was named 'telomeres capping' (Chan and Blackburn, 2002).…”
Section: Discussionmentioning
confidence: 95%
“…Other studies demonstrated an inhibitory effect of IM on PDGF-R-expressing cell lines, suggesting that this effect was mediated mainly through promoting growth arrest rather than apoptosis (Kilic et al, 2000). Although most of telomerase inhibition strategies resulted in decreased proliferation and apoptosis or cell cycle arrest (Hahn et al, 1999;Herbert et al, 1999;Heinrich et al, 2000;Kilic et al, 2000;Boklan et al, 2002;Seimiya et al, 2002;Zaffaroni et al, 2002), other studies showed that inhibition of telomerase was accompanied mainly by the inhibition of cell proliferation rather than cell death. For example, hTR antisense inhibited TA in human pancreatic carcinoma cell line, concomitantly with a significant decrease in proliferation, without a crisis or senescence phenomenon Teng and Fahey, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ectopic expression of telomerase in normal human cells leads to extension of life-span or immortalization of many cell types [18,19]. Inhibition of telomerase in telomerase positive cancer cells can lead to the induction of cell death [20][21][22]. Finally, mutations in either hTR or TERT are associated with many premature aging phenotypes leading to human diseases [23][24][25].…”
Section: Introductionmentioning
confidence: 99%